Evidence for an audience effect in mice: male social partners alter the male vocal response to female cues - Seagraves, Kelly M. (J Exp Biol, 2016)
Mice (Mus musculus) form large and dynamic social groups and emit ultrasonic vocalizations in a variety of social contexts. Surprisingly, these vocalizations have been studied almost exclusively in the context of cues from only one social partner, despite the observation that in many social species the presence of additional listeners changes the structure of communication signals. Here, we show that male vocal behavior elicited by female odor is affected by the presence of a male audience – with changes in vocalization count, acoustic structure and syllable complexity. We further show that single sensory cues are not sufficient to elicit this audience effect, indicating that multiple cues may be necessary for an audience to be apparent. Together, these experiments reveal that some features of mouse vocal behavior are only expressed in more complex social situations, and introduce a powerful new assay for measuring detection of the presence of social partners in mice.